Trabajos académicos : algunas cosas que no - Ubertone, Fermín Pedro (2017)
In this paper the author proposes a series of basic grammatical and writing style recommendations when writing an academic paper, particularly in the postgraduate studies. Also, he gives some practical advice that could not be usually learned from books.